2012
DOI: 10.1371/journal.pone.0044699
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Awareness about Antibiotic Use and Resistance: A Hands-On Project for High School Students

Abstract: BackgroundHealth-promoting education is essential to foster an informed society able to make decisions about socio-scientific issues based on scientifically sustained criteria. Antibiotic resistance is currently a major public health issue. Considering that irrational antibiotic use has been associated with the development and widespread of antibiotic resistant bacteria, educational interventions to promote prudent antibiotic consumption are required.Methodology/Principal FindingsThis study focuses on the outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 54 publications
0
34
0
3
Order By: Relevance
“…Similarly, a recent study in Portugal entitled “Microbiology recipes” showed the importance of educational activities incorporating hands-on activities in science education. This project improved the participants’ understanding of bacteria, antibiotics and antibiotic resistance [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent study in Portugal entitled “Microbiology recipes” showed the importance of educational activities incorporating hands-on activities in science education. This project improved the participants’ understanding of bacteria, antibiotics and antibiotic resistance [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Educational interventions on health aspects aimed at school going children have been reported to impart healthier lifestyle [3] . Promoting knowledge through hands-on educational programs on antimicrobial use in children is reported to improve awareness about infection prevention which is termed to be crucial in allowing them to take conscious decisions on appropriate antimicrobial use [11] [12]. The National Institute of Clinical Excellence (NICE) and research findings from Europe recommend that schools should teach about prevention of infections, self-care, appropriate antimicrobial use and stressed the need for health interventions in early childhood [13] .…”
Section: Introductionmentioning
confidence: 99%
“…However, results from the last 2016 Eurobarometer survey, as well as from a cross-sectional study recently conducted in Italy, have shown that many adults still have serious misunderstandings about antibiotics and that children's basic knowledge of antibiotic use is poor [5,6]. Thus, in the past few years, a variety of educational campaigns, such as the "European Antibiotic Awareness Day" led by the European Centre for Disease Prevention and Control, and many other programs have been proposed to improve global awareness of AMR in general public, including school-aged children [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Through this approach, it was easy to motivate and interest young students, bringing scientific education and key learning concepts on microbiology closer to this young audience. Previous studies have shown that the use of interactive activities can greatly improve public knowledge on specific health issues such as microbial infections, antimicrobial resistance and prudent antibiotic use [7,[15][16][17]. Furthermore, 7 the direct contact and dialogue of microbiologists, who offered all the participants their scientific knowledge and expertise with an exchange of questions and answers, were considered extremely successful either by young students or by the teachers.…”
mentioning
confidence: 99%
See 1 more Smart Citation